Dispersion and rheology for direct writing lead‐based piezoelectric ceramic pastes with anisotropic template particles. Issue 11 (20th July 2020) - Walton, Rebecca L.; Fanton, Mark A.; Meyer, Richard J.; Messing, Gary L.
Abstract: Controlling the rheology of direct writing pastes is essential for producing high quality printed ceramics. Ceramic pastes were formulated to explore the relation between surface chemistry and rheology of complex pastes of Pb(In1/2 Nb1/2 )O3 ‐Pb(Mg1/3 Nb2/3 )O3 ‐PbTiO3 (PIN‐PMN‐PT) powder, large BaTiO3 (BT) platelet particles, and a commercial poly(acrylic) acid‐based binder system. Zeta potential of the ceramic powder, the conformation of the poly(acrylic) acid, and the effect of these factors on rheology were evaluated as a function of suspension pH. Effective dispersion and amenable rheology for direct writing were achieved at mixing pH 5. Additions of 0.3 to 2.6 vol% BT tabular particles dramatically altered the rheology of the pastes due to the shear alignment of the BT particles. Powder‐organic interactions and the size and concentration of BT platelet particles can be tailored to direct write either space‐filling filaments to form dense ceramics or non‐flowing filaments to form spanning ceramic structures.